A canine model of reversible urethral sphincter insufficiency - Pourya Shokri; Shahin Tabatabaei; Seyed Amir Mohsen Ziaee; Mir Sepehr Pedram; Mohammad Mehdi Dehghan; Nasser Shakhssalim (Animal Models and Experimental Medicine)
Abstract This study developed an animal model with internal and external urethral sphincter insufficiency by bypassing the sphincter without major damage so that the animal under study can return to normal life after the study. There is a need for a reliable, applicable, and reproducible animal model for studying urinary incontinency disease due to incorrect sphincter function. Seven adult male dogs were used for this study. The urethral sphincter was bypassed by inserting a catheter between the bladder neck and the distal sphincter. The animals' physical condition was closely monitored for 9 weeks, and standard urodynamic and radiologic studies were performed before and 1–2 months after surgery. The animals were killed at 9 weeks after surgery for pathological assessment. Catheter placement caused complete incontinence in the animal, with urodynamic assessments indicating that the animal was unable to control urination and radiological assessments indicating an empty bladder with a residual volume of 50 ± 10 cc. Tissue analysis did not show significant histological damage and inflammation. The study shows that by bypassing the urethral sphincter, which is a reliable and reproducible method, an animal model of urinary incontinence can be developed, which can be used in various studies such as assessing the adequacy of artificial sphincter function. The animals under study did not have any permanent defect, so they were able to return to their normal life.